2000
DOI: 10.1128/mcb.20.2.478-487.2000
|View full text |Cite
|
Sign up to set email alerts
|

CLN1 and Its Repression by Xbp1 Are Important for Efficient Sporulation in Budding Yeast

Abstract: Xbp1, a transcriptional repressor of Saccharomyces cerevisiae with homology to Swi4 and Mbp1, is induced by stress and starvation during the mitotic cycle. It is also induced late in the meiotic cycle. Using RNA differential display, we find that genes encoding three cyclins (CLN1, CLN3, and CLB2), CYS3, and SMF2 are downregulated when Xbp1 is overexpressed and that Xbp1 can bind to sequences in their promoters. During meiosis, XBP1 is highly induced and its mRNA appears at the same time as DIT1 mRNA, but its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 54 publications
2
40
0
Order By: Relevance
“…5). XBP1 codes for a repressor of CLN1 and CLB2 expression during sporulation, and XBP1 expression is induced by diverse stresses (34,35). We found that XBP1 mRNA levels were increased eightfold in nitrogen-limited chemostats compared to rich-medium chemostats.…”
Section: Vol 21 2001mentioning
confidence: 66%
See 1 more Smart Citation
“…5). XBP1 codes for a repressor of CLN1 and CLB2 expression during sporulation, and XBP1 expression is induced by diverse stresses (34,35). We found that XBP1 mRNA levels were increased eightfold in nitrogen-limited chemostats compared to rich-medium chemostats.…”
Section: Vol 21 2001mentioning
confidence: 66%
“…Xbp1 is synthesized in response to diverse types of stress and it is required for repression of CLN1 and CLB2 transcription during sporulation (34,35). We showed that XBP1 is highly expressed during growth of wild-type yeast cells in nitrogen-limited chemostats (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, ClnCdc28 activity prevents the accumulation of Ime1 in the nucleus of mitotic cells, and ectopic expression of IME1 in cells depleted of G 1 cyclins is sufficient to promote meiosis and sporulation in rich medium (8). G 1 cyclins are rapidly downregulated in yeast cells deprived of nitrogen (8,13,29). Because depletion of G 1 cyclins mimics nitrogen starvation, we proposed that G 1 cyclins would transmit nutritional signals to Ime1 function (8).…”
mentioning
confidence: 99%
“…In reality, the frequency of sex generally depends on the condition of an individual, a pattern found broadly across both facultatively sexual prokaryotes and eukaryotes (Bell 1982). Individuals that are starved undergo sex at higher rates in a wide variety of organisms, including bacteria (Dubnau 1991;Redfield 1993;Jarmer et al 2002;Foster 2005), yeast (Kassir et al 1988;Mai and Breeden 2000), Chlamydomonas reinhardtii (Harris 1989), and daphnia (in combination with photoperiod and density cues; Kleiven et al 1992). Cells with DNA damage have also been shown to undergo sex at higher rates in viruses (Bernstein 1987), bacteria (Wojciechowski et al 1989), and yeast (Bernstein and Johns 1989).…”
mentioning
confidence: 99%